Pripovedna ekfraza kot možnost pozorne pripovedi v sodobnem slovenskem romanu - Rakovec, Ana (Jezik in slovstvo, 2025)
Contemporary Slovene novels frequently explore art, and some even portray it as the ultimate solid entity in the contingency of the world, while searching for new expressive possibilities for an inclusive narrative that would transcend the anthropocentric view. One possible narrative approach is the use of narrative ekphrasis, which appears in three Slovene novels published after 2020: the novel Sin in sin Son and Son (2020) by Sarival Sosič, Na drugem koncu sveta On the Other Side of the World (2020) by Vincenc Gotthardt, and Tri barve za eno smrt Three Colours for One Death (2023) by Janja Rakuš. Ekphrastic images that verbalize works of art in three different ways evoke narrative empathy and represent the possibility of a tender narrative. They enable a synergistic connection of both multimedia and genre worlds, reveal the (metaphorical) depths of (multi)messaging, allude to the experience of transcendence, and introduce new multimodal elements into the narrative, thereby altering the concept of the autonomy of the fictional world. By introducing narrative ekphrasis, these contemporary Slovene novels adopt a socio-critical stance towards art, humanity and human indifference, memory and forgetting, or minority entities.
Keywords: contemporary Slovene novel; ekfraza; ekphrasis; narrative ekphrasis; narrative empathy; narrator; pripovedna ekfraza; pripovedna empatija; pripovedovalec; Slovene literature; slovenska književnost; sodobni slovenski roman